Standardizing training for Pressurized Intraperitoneal Aerosol Chemotherapy. Issue 12 (December 2020) - Alyami, Mohammad; Sgarbura, Olivia; Khomyakov, Vladimir; Horvath, Philipp; Vizzielli, Giuseppe; So, Jimmy; Torrent, Juan; Delgadillo, Xavier; Martin, David; Ceelen, Wim; Reymond, Marc; Pocard, Marc; et al.
Abstract: Background: PIPAC is a novel mode of intraperitoneal drug delivery for patients with peritoneal cancer (PC). PIPAC is a safe treatment with promising oncological results. Therefore, a structured training program is needed to maintain high standards and to guarantee safe implementation. Methods: An international panel of PIPAC experts created by means of a consensus meeting a structured 2-day training course including essential theoretical content and practical exercises. For every module, learning objectives were defined and structured presentations were elaborated. This structured PIPAC training program was then tested in five courses. Results: The panel consisted of 12 experts from 11 different centres totalling a cumulative experience of 23 PIPAC courses and 1880 PIPAC procedures. The final program was approved by all members of the panel and includes 12 theoretical units (45 min each) and 6 practical units including dry-lab and live surgeries. The panel finalized and approved 21 structured presentations including the latest evidence on PIPAC and covering all mandatory topics. These were organized in 8 modules with clear learning objectives to be tested by 12 multiple-choice questions. Lastly, a structured quantifiable (Likert scale 1–5) course evaluation was created. The new course was successfully tested in five courses with 85 participants. Mean overall satisfaction with the content was rated at 4.79 (±0.5) with at 4.71 (±0.5) and at 4.61 (±0.7), respectively for course length and the balance between theory and practice. Conclusions: The proposed PIPAC training program contains essential theoretical background and practical training enabling the participants to safely implement PIPAC.